What is the coefficient of x 9 9 in the expansion ( x − 1 ) ( x − 3 ) ( x − 5 ) ⋯ ( x − 1 9 9 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There are 1 0 0 terms in the expansion so the x 9 9 terms are formed by the x ′ s from 9 9 brackets and the number from 1 bracket. This gives the answer as:
i = 1 ∑ 1 0 0 − ( 2 i − 1 ) = − ( 2 i = 1 ∑ 1 0 0 i − i = 1 ∑ 1 0 0 1 ) = − ( 2 × 2 ( 1 0 0 ) ( 1 0 0 + 1 ) − 1 0 0 ) = − 1 0 0 0 0
Good approach isolating the x 9 9 term.
Typo: First line, x 9 9
Problem Loading...
Note Loading...
Set Loading...
Using Vieta's formulas , we have:
n = 1 ∏ 1 0 0 ( x − ( 2 n − 1 ) ) = x 1 0 0 − x 9 9 k = 1 ∑ 1 0 0 ( 2 k − 1 ) + x 9 8 j , k = 1 , j = k ∑ 1 0 0 ( 2 j − 1 ) ( 2 k − 1 ) + . . . + n = 1 ∏ 1 0 0 ( 2 n − 1 )
The coefficient of x 9 9 is − 1 × sum of roots or − k = 1 ∑ 1 0 0 ( 2 k − 1 ) = − 2 1 0 0 ( 1 + 1 9 9 ) = − 1 0 0 0 0